"Like Yeast in Dough": The Church–World Relationship in the Evolving Thought of Marie-Dominique Chenu. (December 2020) - Kate Holman, Mary
During his Parisian "exile" from 1942 to 1954, Marie-Dominique Chenu's experiences with worker communities transformed his vision of the church–world relationship. This article highlights the overlooked social dimension of Chenu's pre-conciliar thought, tracing his shift from a "New Christendom" ecclesiology towards a church in a state of mission and his growing call for ecclesial structural change in light of changing social structures. These life experiences would lead him to advocate for a church that reads and responds to the "signs of times."